Integrating technology in mental healthcare practice: A repeated cross-sectional survey study on professionals’ adoption of Digital Mental Health before and during COVID-19 - Feijt, Milou; de Kort, Yvonne; Westerink, Joyce; Bierbooms, Joyce; Bongers, Inge; IJsselsteijn, Wijnand (Frontiers in Psychiatry, 2023)
As a consequence of the outbreak of the COVID-19 global pandemic in the Spring of 2020, large-scale social distancing measures were implemented, resulting in the forced adoption of online or digital forms of psychological treatment. This sudden transition to digital care offered a unique opportunity to investigate if and how this experience impacted mental healthcare professionals' perceptions and use of Digital Mental Health tools. The current paper presents findings of a repeated cross-sectional study consisting of three iterations of a national online survey conducted in [COUNTRY]. This survey contained open and closed questions on professionals' adoption readiness, frequency of use, perceived competency, and perceived value of Digital Mental Health collected in 2019 (before the pandemic), in 2020 (after the first wave), and in 2021 (after the second wave). The inclusion of data gathered prior to the COVID-19 pandemic offers a unique window to assess how professionals' adoption has developed through this transition from voluntary to mandatory use of Digital Mental Health tools. Our study also re-assesses the drivers, barriers, and needs of mental healthcare professionals after having gained experience with Digital Mental Health. In total, 1039 practitioners completed the surveys (Survey 1: n=432, Survey 2: n=363, Survey 3: n=244). Results indicate that compared to the period before the pandemic, there was a particularly large increase in use, competency, and perceived value regarding videoconferencing. Small differences were also found for some other basic tools that were crucial for the continuation of care, such as e-mail, text messaging, and online screening, but not for more innovative technologies, such as Virtual Reality and biofeedback. Many practitioners reported to have gained skills regarding Digital Mental Health and experienced several benefits of it. They expressed the intention to continue with a blended approach, using Digital Mental Health tools in combination with face-to-face care, focused on situations in which they found it to have specific added value, such as when clients are unable to travel. Others were less satisfied with the technology-mediated interactions and remain more reluctant to future use of DMH. Implications for broader implementation of Digital Mental Health and future research are discussed.